Modular mechanisms of immune priming and growth inhibition mediated by plant effector-triggered immunity - Himanshu Chhillar; Hoang Hung Nguyen; Pei-Min Yeh; Jonathan D.G. Jones; Pingtao Ding (Cell Reports)
Summary: Excessive activation of effector-triggered immunity (ETI) in plants inhibits plant growth and activates cell death. ETI mediated by intracellular Toll/interleukin-1 receptor/resistance protein (TIR) nucleotide-binding, leucine-rich repeat receptors (NLRs) involves two partially redundant signaling nodes in Arabidopsis, ENHANCED DISEASE SUSCEPTIBILITY 1-PHYTOALEXIN DEFICIENT 4-ACTIVATED DISEASE RESISTANCE 1 (EDS1-PAD4-ADR1) and EDS1-SENESCENCE-ASSOCIATED GENE 101-N REQUIREMENT GENE 1 (EDS1-SAG101-NRG1). Genetic and transcriptomic analyses show that EDS1-PAD4-ADR1 primarily enhances immune component abundance and is critical for limiting pathogen growth, whereas EDS1-SAG101-NRG1 mainly activates the hypersensitive response (HR) cell death but is dispensable for immune priming. This study enhances our understanding of the distinct contributions of these two signaling modules to ETI and suggests molecular principles and potential strategies for improving disease resistance in crops without compromising yield.